2008
DOI: 10.1080/09658210802007493
|View full text |Cite
|
Sign up to set email alerts
|

Recognition memory for valenced and arousing materials under conditions of divided attention

Abstract: Two experiments are reported that examined the effect of both valence and arousal on recognition memory performance. Each experiment used two classes of negative items that differed in arousal, as well as a neutral and non-arousing set of items. In Experiment 1 a difficult divided attention task was crossed with the learning and test phases of the experiment. In Experiment 2 encoding time was manipulated and remember-know judgements were collected. The emotional enhancement effect often found with verbal mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 22 publications
5
28
1
Order By: Relevance
“…This latter observation indicates that it is difficult to eliminate EEM by using a distractor task that is designed to prevent elaboration. Further, the results in the present experiments are consistent with the findings reported by other researchers (Clark-Foos & Marsh, 2008;Kensinger & Corkin, 2004;Kern et al, 2005). Taken together, it is reasonable to assume that elaboration plays a minor role in remembering negatively arousing picture.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…This latter observation indicates that it is difficult to eliminate EEM by using a distractor task that is designed to prevent elaboration. Further, the results in the present experiments are consistent with the findings reported by other researchers (Clark-Foos & Marsh, 2008;Kensinger & Corkin, 2004;Kern et al, 2005). Taken together, it is reasonable to assume that elaboration plays a minor role in remembering negatively arousing picture.…”
Section: Discussionsupporting
confidence: 95%
“…In other words, remembering emotional details does not require rehearsal (or poststimulus elaboration). Other researchers using emotional words (Clark-Foos & Marsh, 2008;Kensinger & Corkin, 2004) also reported that dividing attention does not eliminate EEM when stimuli are negatively arousing.…”
Section: Please Scroll Down For Articlementioning
confidence: 92%
“…The remember-know procedure (Gardiner, 1988;Rajaram, 1993;Tulving, 1985) involves asking subjects to differentiate between responses for which they can recollect contextual details associated with retrieval (i.e., a remember response) and responses that are devoid of these contextual details (i.e., a know response). The assumption is that remember responses are influenced by recollection to a great degree, and know responses are influenced by automatic processing to a great degree (see Clark-Foos & Marsh, 2008;De Goede & Postma, 2008;Kelley & Jacoby, 1998;Rajaram, 1993). Of particular interest was an examination of whether dividing attention reduced the subjective experience of recollection (i.e., remember judgments) but left subjective experience of familiarity (i.e., know judgments) unaffected (Gardiner & Parkin, 1990), a pattern which would parallel findings using the process dissociation procedure (Jacoby, Toth, & Yonelinas, 1993).…”
Section: Remembering and Knowing In Free Recallmentioning
confidence: 96%
“…It is well known that the enhanced memory capability observed for emotional events is due, at least in part, to the amygdala's influence on encoding and storage of hippocampal-dependent memories, as suggested by many studies showing amygdala activation during the encoding of emotional stimuli predicts subsequent retention (Cahill et al, 1996;Canli et al, 2000;Kensinger and Corkin, 2004). While the left amygdala is more responsive to conscious, language-dependent processing (Markowitsch, 1998;Phelps, 2006), the right amygdala has been shown to subserve a system of automatic detection of emotional stimuli (Kensinger and Corkin, 2004;Costafreda et al, 2008), which can be triggered by recognition tasks (Clark-Foos and Marsh, 2008). The right amygdalar activation for recognition compared to recall/imagine tasks may reflect this automatic process in emotional processing.…”
Section: Posterior Parahippocampal Gyrusmentioning
confidence: 99%